Penyelesaian Sengketa Harta Bersama Dengan Harta Bawaan Ketika Terjadi Perceraian - Jhon Kenedi (Institut Agama Islam Negeri Bengkulu, 2019)
The Marriage Agreement functions as a solution to anticipate or avoid injustice in the trial process in the court of the distribution of property, if there is a dispute between husband and wife. Conflicts over the distribution of inheritance sometimes can not be resolved by mediation efforts, even after being processed in the first court (religious court), continues into the court of appeal and cassation. Benefits of a Marriage Agreement in the Settlement of Default Assets, to assist the panel of judges adjudicating a case of inheritance disputes in making the right decision in divorce cases. If a case does not occur, the agreement is useful for separating the status between shared assets and property. If a case / dispute occurs, the marriage agreement is available